A formação do habitus dos acordeonistas estudantes do curso de licenciatura em música da Universidade Federal do Ceará - Gurgel, Danilo Ramalho (2023)
The current project deals with the investigation of the Habitus formation among the accordionist students graduating from the Music Degree course at the Federal University of Ceará (UFC) - Pici Campus, in Fortaleza-CE. It is considered that by investigating the trajectory of accordionists graduated from this course, a significant part of the teaching field of this instrument is described, involving the field of Music Education, both in university education and in basic education. The general objective of this research is to analyze the Habitus formation of the accordionists who have studied in the Music Degree course of the Federal University of Ceará – Campus do Pici, in Fortaleza-CE. The specific objectives are: to investigate the historical context of the spaces occupied by the accordion, interrelated to Music Degree course of the Federal University of Ceará – Campus do Pici, in Fortaleza-CE; to identify the historical factors - from the social origin of the agents - that contributed to becoming accordionists and students of the Music Degree course at the Federal University of Ceará, Pici Campus, in Fortaleza-CE and to analyze the professional integration of the individuals in the role of accordionists and accordion teachers after graduating in the Music Degree course. Bourdieu's praxeology – including the concepts of Habitus, capital and field – constitutes the theoretical foundation of these studies. The research adopts a qualitative approach, based on data collection through semi-structured interviews, in addition to the autobiographical account, based on the life history and formation methodology. Five accordionists contemplate the profile to be researched, including the author of this research. In addition to the autobiographical analysis, three agents were interviewed. When investigating the reports, some categories were evidenced, such as the financial capital of the agents for the acquisition of their first accordion; the previous experience as a professional musician before entering college; access to formal music teaching, in a curricular way, during the period of basic education; contact with music schools, or private teachers specialized in accordion; the non-requirement of the aptitude test for admission to the UFC degree course as a determining factor for the choice of this institution and professional performance after graduation. Regarding the space occupied by the accordion, in the context of this course degree, it was observed, through consultation of official documents and the agents' reports, a minimal attention given by the music course to this aerophone. In order to solve the issue of the "non-space" of this instrument, the data analysis demonstrated the necessity for a professor with expertise in accordion within this graduation course.